Longitudinal associations of academic stress with eating related patterns, nutrition, somatic indicators, and depressive symptoms in university students: A study protocol - Pía Rojas-Cárdenas; Gabriela Nazar; Juan Luis Castillo-Navarrete (PLoS ONE, 2026)
Introduction Academic stress (AS) can be understood as a multidimensional form of chronic stress that has been linked to adverse patterns across physical and mental health in university students. This protocol outlines a longitudinal, observational study to examine within-semester associations between AS and indicators of nutritional status, eating-related patterns, sleep quality, and depressive symptoms. By integrating physiological, behavioral, and psychological indicators within a repeated-measures framework, the study aims to generate evidence that can inform prevention-focused actions and early support strategies in university health contexts. Hypotheses (i) Higher AS will be longitudinally associated with less favorable eating-related patterns, nutritional and somatic indicators, and higher depressive symptoms in university students. (ii) Higher AS will be associated with altered post-awakening cortisol dynamics, specifically a lower cortisol awakening response (CAR) and lower AUCi, together with a higher AUCg, and with higher salivary alpha-amylase (sAA) levels, consistent with stress-related activation of HPA-axis and sympathetic pathways. Design and participants A longitudinal, observational, nonexperimental design with repeated measurements will be implemented across three assessment cycles during an academic semester. A feasibility-based convenience sample will be recruited from undergraduate students (2nd to 4th year) enrolled in the Faculty of Medicine, University of Concepción (Chile). Students receiving psychological or pharmacological treatment will be eligible to reflect real-world heterogeneity and support ecological validity. Methods Data will be collected through standardized questionnaires, nutritional assessments, biological sampling, and wearable-derived somatic indicators. Electronic surveys administered via REDCap will assess AS, perceived stress, eating-related patterns, and depressive symptoms. Diet will be assessed through interviewer-administered nutritional interviews, including repeated 24-hour dietary recalls treated as time-specific observations and modeled longitudinally as time-varying measures, and complemented by diet-quality and dietary inflammatory potential indices. Wearable devices will record nonclinical somatic indicators, including heart rate, oxygen saturation, and sleep-related metrics during monitoring periods. Saliva will be collected twice per week during each assessment cycle to quantify salivary cortisol dynamics and sAA activity, and peripheral blood samples obtained at baseline and end of semester will be used to determine lipid profile, fasting glucose, albumin, globulin, and total proteins. Statistical analysis Analyses will include descriptive and bivariate summaries, followed by multivariable models appropriate to outcome type. Longitudinal associations will be examined using mixed-effects models, and temporal cross-lagged associations will be explored using random-intercept cross-lagged panel models across the three assessment cycles. All inferences will be framed as associational given the observational design. Expected results Rather than prespecifying outcomes, this protocol is expected to generate longitudinal evidence on how within-semester variation in AS aligns with eating-related patterns, diet, nutritional and somatic indicators, depressive symptoms, and stress-related physiological indicators (salivary cortisol dynamics and sAA activity). The integrated, feasibility-oriented measurement framework may serve as a replicable template for future research and inform prevention-focused actions to support student well-being in university settings.